2015
DOI: 10.1080/10875549.2014.991890
|View full text |Cite
|
Sign up to set email alerts
|

Learning Problems as Predictors of Depressive Symptomology in Women TANF Recipients

Abstract: Little is known about relationships between barriers to self-sufficiency in the Temporary Assistance for Needy Families (TANF) population. This study utilized ordinary least squares regression to analyze secondary data from a nonprobability sample of 2,156 women TANF recipients to examine learning problems as a predictor of depressive symptomology. After controlling for substance abuse, intimate partner violence victimization, physical health problems, demographics, and difficulty with interpersonal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, Quittner, Glueckauf, and Jackson (1990) found that social support mediated the relationship between childhood stressors and psychological wellbeing and did not moderate the effect. Similarly, Wahler Otis, and Leukefeld (2015) found that perceptions of negative social interactions mediated the relationship between learning problems on depressive symptoms.…”
Section: Social Support: Moderator or Mediatormentioning
confidence: 91%
“…For example, Quittner, Glueckauf, and Jackson (1990) found that social support mediated the relationship between childhood stressors and psychological wellbeing and did not moderate the effect. Similarly, Wahler Otis, and Leukefeld (2015) found that perceptions of negative social interactions mediated the relationship between learning problems on depressive symptoms.…”
Section: Social Support: Moderator or Mediatormentioning
confidence: 91%
“…Likewise, women receiving government benefits have experienced a higher prevalence of IPV and IPV-related health issues (An & Choi, 2019; Yoshihama et al, 2006). Experiencing IPV may limit a woman's ability to comply with minimum work requirements mandated by the US federal government to receive the TANF program benefits (Booshehri et al, 2018; Gallagher, 2011; Spencer et al, 2020; Wahler et al, 2015). Hsu (2017) examined the association between the timing of TANF transfer payments and reporting IPV to the police across 21 states in the US.…”
Section: Discussionmentioning
confidence: 99%